2020
DOI: 10.1002/bmc.4872
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive and rapid UHPLC–MS/MS method for simultaneous quantification of nine compounds in rat plasma and application in a comparative pharmacokinetic study after oral administration of Xuefu Zhuyu Decoction and nimodipine

Abstract: Xuefu Zhuyu Decoction (XFZYD) is a traditional Chinese medicine prescription used for the clinical treatment of traumatic brain injury (TBI). The purpose of this work was to develop a sensitive and rapid UHPLC–MS/MS method to simultaneously study the pharmacokinetics of nimodipine and eight components of XFZYD, namely, amygdalin, hydroxysafflor yellow A, rutin, liquiritin, narirutin, naringin, neohesperidin and saikosaponin A, in rats with and without TBI. Multiple reaction monitoring was highly selective in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…It is necessary to consider the different natural therapeutic methods. Xuefu Zhuyu Decoction (XFZYD), a classical prescription, has been widely used in clinical to treat cardiac-cerebral vascular disease ( Zhang et al, 2004 ; Yang T. et al, 2019 ; Fu et al, 2020 ; Wang et al, 2020a ). Our previous studies reported that XFZYD could reduce neurological deficits after TBI via inflammatory inhibition ( Xing et al, 2016 ) and improve the long-term prognosis post-TBI via synaptic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to consider the different natural therapeutic methods. Xuefu Zhuyu Decoction (XFZYD), a classical prescription, has been widely used in clinical to treat cardiac-cerebral vascular disease ( Zhang et al, 2004 ; Yang T. et al, 2019 ; Fu et al, 2020 ; Wang et al, 2020a ). Our previous studies reported that XFZYD could reduce neurological deficits after TBI via inflammatory inhibition ( Xing et al, 2016 ) and improve the long-term prognosis post-TBI via synaptic regulation.…”
Section: Introductionmentioning
confidence: 99%